2011
DOI: 10.1177/0363546511428068
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparison of Conventional and Remnant-Preserving Transtibial Single-Bundle Posterior Cruciate Ligament Reconstruction Combined With Posterolateral Corner Reconstruction

Abstract: Techniques combining remnant-preserving transtibial single-bundle PCL reconstruction with posterolateral corner reconstruction resulted in somewhat better activity-related outcomes compared with those of approaches without remnant preservation. However, incorporation of remnant preservation does not appear to provide increased posterior stability or result in clinically superior outcomes versus those of techniques without remnant preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…If remnant fibers are well preserved, it contributes to stability, aids in the restoration of proprioception by saving mechanoreceptors, and prevents the killer-turn effect by acting like a cushion. 4,26,31,56 Postoperative proprioception recovered similarly to that of the uninvolved side, and we found a high rate of complete healing and synovialization on MRI and second-look arthroscopic surgery. We assumed that remnant PCL fibers would heal with the graft and provide less loosening of the graft induced by the killer turn and restoration of sensation for joint motion as well as position.…”
Section: Discussionsupporting
confidence: 56%
“…If remnant fibers are well preserved, it contributes to stability, aids in the restoration of proprioception by saving mechanoreceptors, and prevents the killer-turn effect by acting like a cushion. 4,26,31,56 Postoperative proprioception recovered similarly to that of the uninvolved side, and we found a high rate of complete healing and synovialization on MRI and second-look arthroscopic surgery. We assumed that remnant PCL fibers would heal with the graft and provide less loosening of the graft induced by the killer turn and restoration of sensation for joint motion as well as position.…”
Section: Discussionsupporting
confidence: 56%
“…20 In addition, the level of return to activity after ACL reconstruction was assessed according to the method defined by a previous study. 22 Patients who returned to the level of their preinjury activity according to the Tegner activity scale at 2 years after ACL reconstruction were considered as having accomplished return to activity and patients who returned to the level of their preinjury activity or just the one level below that according to the Tegner activity scale at 2 years after ACL reconstruction were considered as having accomplished near-return to activity.…”
Section: Clinical Assessmentsmentioning
confidence: 99%
“…29,30 There were many studies that reported the outcomes of PCLR that included patients with posterolateral corner (PLC) injuries. 23,31,32 In PCLR the identification of concomitant injuries of the PLC is important for optimizing the surgical and clinical outcomes. We believed that the role of the PCL remnant would be clarified by comparing isolated PCLR with versus without remnant preservation.…”
Section: Remnant Preservationmentioning
confidence: 99%